Endometrial Carcinoma Presenting with an Isolated Osseous Metastasis: A Case Report - Tounsi, Nesrine; Zemni, Ines; Saadalah, Fatma; Slimane, Maher; Boujelbene, Nadia; Ayadi, Mohamed ali; Rhiad, Chargui; Khaled, Rahal (Gynecology Obstetrics & Reproductive Medicine, 2022)
Patients with advanced endometrial cancer had generally a poor prognostic with a median survival often less than one year. Isolated bone metastases as the first sign of the disease of endometrial cancer was a very exceptional situation rarely described in the literature. The goal of this report is to describe the management of this rare site of metastases and to reviewed Clinic pathological features and prognosis of isolated bone metastases. We present a case of a 56-year-old woman treated for endometrial cancer with isolated ribs bone metastases. She was complaining about progressive right rib pain as a first sign of the disease of endometrial cancer. She had a biopsy of the lesion in the last right thoracic rib. This has proved a metastatic adenocarcinoma compatible with an endometrial primary cancer. An endometrial biopsy showed moderately differentiated endometrioid adenocarcinoma. Imagery did not reveal any other sites of metastatic disease. The patient underwent bilateral salpingo-oophorectomy and hysterectomy, peritoneal washing, omentectomy, bilateral pelvic and par aortic lymphadenectomy. In addition, a right thoracotomy was carried out and complete surgical excision of the rib mass was successfully performed. Adjuvant chemotherapy was administrated. The patient is clinically free of disease 10 months following diagnosis. Single-bone extrauterine metastatic site and local disease limited to the uterus had better survival outcomes than Stage IVb endometrial cancer with multiple metastatic sites. Therefore, the patient treated with surgery with a clear margin continued to behave as early-stage endometrial cancer.